Pembelajaran Kebersihan dengan Menerapkan Sistem Zero Waste di SLBIT Ibnu Mas’ud Singkawang - Tokimin Tokimin (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2022)
Cleanliness is the most important part of the learning ecosystem in special education units. Instilling good values ​​and practices regarding cleanliness is a real application of practicing the concept of taharah. The current paradigm in managing waste with a zero waste system is the 3R method (Reuse, Reduce and Recycle). The main purpose of habituation to maintain a clean environment is to create a habit that is instilled in students from an early age with a system (Reuse, Reduce and Recycle). Learning and applying hygiene with the 3R system for SLBIT Ibnu Mas’ud Singkawang students, West Kalimantan. Looking at the culture and analyzing the problem with 4 criteria (environment, capability, system, and source), the main problem in implementing it is that it is important for students to be reminded every day to manage personal waste and other people’s waste in the school environment as a result of the start of the practical process of handling waste with a system. zero waste, does not support facilities in waste management with zero waste, how to manage waste for parents with a zero waste system, and the skill of students in managing waste independently. The method applied is by direct instruction and clean action. The result is the creation of a clean, healthy environment and reduced waste and use of it into recycled goods. ABSTRAKKebersihan adalah bagian terpenting dari ekosistem pembelajaran pada satuan pendidikan khusus. Penanaman nilai dan praktik baik mengenai kebersihan merupakan aplikasi nyata mengamalkan konsep taharah. Paradigma kekinian dalam mengelola sampah dengan sistem zero waste adalah dengan metode 3R (Reuse, Reduce dan Recycle) Pada praktiknya sistem ini mampun dalam mengelola sampah, bahkan pada titik nol (zero) tiada lagi sampah yang dihasilkan dilingkungan. Tujuan utama pembiasaan menjaga lingkungan bersih ialah menjadikan habit yang tertanam sejak didini pada murid dengan sistem (Reuse, Reduce dan Recycle). Pembelajaran dan penerapan kebersihan dengan sistem 3R pada murid SLBIT Ibnu Mas’ud Singkawang, Kalimantan Barat. Melihat budaya dan analisa permasalahan dengan 4 kriteria (lingkungan, kemampuan, sistem, dan sumber), masalah utama dalam menerapkan, yaitu murid penting setiap hari diingatkan mengelola sampah pribadi dan orang lain di lingkungan sekolah sebagai akibat dari bermulanya proses praktik dalam menangani sampah dengan sistem zero waste, belum mendukung fasilitas dalam pengelolaan sampah dengan zero waste, cara pengelolaan sampah bagi orang tua murid dengan sistem zero waste, serta terampilnya murid dalam mengelola sampah secara mandiri. Cara yang diterapkan ialah dengan instruksi langsung dan aksi bersih. Hasilnya adalah terciptanya lingkungan bersih, sehat dan berkurangnya sampah dan memanfaatkannya menjadi barang daur ulang. Kata kunci: Kebersihan, Zero Waste, SLBIT Ibnu Mas’ud